Indonesian Learners’ Phonological Errors in English Pronunciation: A Literature Review - Mutiara Qalbiyah Marfa; Suci Rahayu; Siti Syahira (JOURNAL SAINS STUDENT RESEARCH, 2026)
Pronunciation plays a crucial role in achieving intelligibility and communicative competence in English as a Foreign Language (EFL) contexts. However, Indonesian learners frequently experience difficulties in producing certain English sounds due to substantial differences between Indonesian and English phonological systems. This study aims to identify the most common phonological errors made by Indonesian learners in English pronunciation and to examine the factors contributing to these errors. Employing a qualitative literature review design, this study synthesizes findings from previous research published between 2020 and 2025 concerning pronunciation difficulties among Indonesian EFL learners. Relevant studies were collected through academic databases and analyzed using thematic analysis to identify recurring error patterns, underlying causes, and research trends. The findings reveal that the most frequent phonological errors involve the substitution of the English consonants /θ/, /ð/, and /v/ with more familiar Indonesian sounds. These errors are primarily influenced by first language interference, articulatory difficulty, limited exposure to authentic pronunciation models, and insufficient pronunciation-focused instruction. The review also highlights a significant imbalance in the existing literature, which predominantly focuses on segmental pronunciation errors while providing limited attention to suprasegmental features such as stress, rhythm, and intonation. This study contributes to the field by synthesizing fragmented findings, identifying research gaps, and emphasizing the need for more comprehensive pronunciation instruction in Indonesian EFL contexts. The findings are expected to provide valuable insights for researchers, language educators, and curriculum developers seeking to improve pronunciation teaching and learning outcomes.